IMPLEMENTING SOCIAL MEDIA MARKETING STRATEGY FOR MICRO-ENTERPRISE IN FASHION RETAIL - Lady, Lady; Melsen, Fandion; Cuandra, Fendy (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2024)
This research aimed to enhance the online presence of Satia Collection, a micro-enterprise in Batam, Indonesia, through strategic use of social media platforms. Social media accounts were established on Instagram, Facebook, Linktree, and Canva, along with a new brand logo and Google Maps registration to improve customer accessibility. The results showed a significant increase in reach and in-teraction on Instagram, along with a notable rise in WhatsApp messages through Instagram and Facebook links. The implementation of Instagram ads led to tre-mendous customer engagement, demonstrating the effectiveness of digital mar-keting strategies. The study highlights the importance of content quality over fre-quency in driving user engagement and underscores the need for retail entrepre-neurs to leverage technological advancements. Facebook, WhatsApp, and Insta-gram emerged as the most-used social media networks, with WhatsApp playing a crucial role in customer-centered marketing due to its affordability and ease of use.